Assessment of Land Suitability in Highly Area of Ende, East Nusa Tenggara, Indonesia, as a Basic Strategy for Growing Coffee (Coffea arabica) - Mujiyo, Mujiyo; Lutfi, Hilda Fadhila; Herawati, Aktavia; Cahyono, Ongko; Wahyuni, Sri; Mutiara, Charly; Lanamana, Willybrodus (Fakultas Pertanian Universitas Padjadjaran, 2025)
Ende Sub-District, East Nusa Tenggara, has various topographies with an altitude of 0-1,100 m asl that can potentially grow Arabica coffee. Still, there is no information available regarding the suitability of the land. This study aims to evaluate the actual land suitability of Arabica coffee based on soil and environmental characteristics. The research method is descriptive explorative through a field survey approach supported by laboratory analysis. Determination of SMU (soil map unit) was carried out by purposive sampling through boring at 31 points, then classified based on soil type to obtain five pedons that represent SMU in Ende Sub-District. Soil sampling was carried out on each layer of each pedon. Data analysis used ANOVA and Pearson correlation tests to determine the determining factors that influence the land suitability class of Arabica coffee. The evaluation results showed that the actual land suitability for Arabica coffee was marginally suitable (S3) and unsuitable (N) classes, with limiting factors, i.e. average temperature, altitude, length of dry period, drainage, base saturation, available P, slope, and erosion hazard. The results of the ANOVA test showed that altitude significantly affected the land suitability class for Arabica coffee, with the best land suitability class at an altitude of 800-1,100 masl. Based on the correlation between land suitability class and land characteristic parameters, the determining factors for land suitability class include average temperature, humidity, drainage, texture, coarse material, total N, available K, erosion hazard, surface rocks, and rock outcrops. Land improvement recommendations are based on making an irrigation system, providing shade plants, N fertilization (urea fertilizer), K fertilization (KCl fertilizer), and terracing.